Computational study of heterocyclic anticancer compounds through nbo method - Shekarkhand, Marzieh; Zare, Karim; Monajjemi, Majid; Tazikeh-Lemeski, Elham; Sayadian, Masoumeh (Nexo Revista Científica, 2022)
In the present study NBO method contain the HOMO and the LUMO energies are calculated for 10 different heterocycles anticancer drug using B3LYP/6-31G(d,p). Frontier molecular orbitals (HOMO and LUMO) and Molecular Electrostatic Potential map of the compound was produced by using the π stacking of structures and anticancer activity of molecules. The NBO analysis was suggested that the molecular system contains π- π interaction, strong conjugative interactions and the molecule become more polarized owing to the movement of π-electron cloud from donor to acceptor. NBO, HOMO and LUMO energies, were investigated and Anticancer activity of Aromatic Heterocyclic compounds was investigated by NBO study and result was compared with our previous study about NICS and S-NICS of these 10 anticancer drug. the HOMO/LUMO gap of the heterocycle anticancer drug is significantly different from each other. The NBO method is used in both symmetric and asymmetric molecules and provides accurate information on the aromatics of the compound, especially the heterocyclic rings. It also provides accurate information in protected areas. Molecule 8 has the highest amount of HOMO and therefore aromaticity among the studied compounds which confirms the result of molecular orbital examination.